HOTS-Resyenvair: Pengembangan Pembelajaran Sistem Respirasi Manusia Berbasis Masalah Pencemaran Lingkungan Hidup di Udara - Ichsan, Ilmi Zajuli; Fatimah, Okta Zenita Siti (Jurnal Biotek, 2022)
Learning natural sciences on the topic of the respiratory system requires innovation. Science learning and innovation can be done by integrating the topic of the human respiratory system and the problem of air pollution. This integration is expected to improve higher-order thinking skills (HOTS) in students. This research aimed to develop an innovative assessment instrument related to the Higher Order Thinking Skills of Human Respiratory System based on Environmental Pollution Problem in Air (HOTS-Resyenvair) for elementary school students. It was an integration between science learning and environmental education. The ADDIE model was applied as the research and development methodology, but the implementation of the research only goes as far as the development stage. According to the findings of this study, the HOTS-Resyenvair instrument consisted of 12 questions derived from 6 indicators based on HOTS aspects adapted from Anderson’s taxonomy. The use of HOTS-Resyenvair as an innovative tool in learning needs to be done to improve students’ abilities to solve respiratory system problems based on environmental pollution problems in the air. The validation results from experts and teachers on HOTS-Resyenvair. are in the suitable category to be used in learning. This study concluded that the HOTS-Resyenvair instrument developed is valid and suitable for science learning.